The changing shape of youth justice: models of practice - Smith, Roger (Criminology & criminal justice, 2019)
This article reports on a two-year investigation, which maps out contemporary approaches to the delivery of youth justice in England, in light of substantial recent changes in this area of practice. The findings are derived from a detailed examination of youth offending plans and a series of corroborative semi-structured interviews with managers and practitioners from selected youth offending services. Our inquiry has enabled us to develop a detailed three-fold typology of youth justice agencies’ orientations towards practice, represented as ‘offender management’, ‘targeted intervention’ and ‘children and young people first’; as well as a small number of ‘outliers’ where priorities are articulated rather differently. Our findings enable us to reflect on this evidence to suggest that there are a number of ‘models’ of youth justice practice operating in parallel; and that there does not appear at present to be the kind of ‘orthodoxy’ in place which has sometimes prevailed in this field. We also raise doubts about previous representations of unified models of youth justice presumed to be operative at national or jurisdictional levels. We conclude with a number of further observations about the combined effect of current influences on the organization and realization of youth justice, including the growing emphasis on localized responsibility for delivery and increasingly complex expectations of the service context.